2009
DOI: 10.1521/aeap.2009.21.4.372
|View full text |Cite
|
Sign up to set email alerts
|

Unseen and Unheard: Predictors of Sexual Risk Behavior and HIV Infection among Men Who Have Sex With Men in Chennai, India

Abstract: In India men who have sex with men (MSM) are stigmatized, understudied, and at high risk for HIV. Understanding the impact of psychosocial issues on HIV risk behavior and HIV infection can help shape culturally relevant HIV prevention interventions. Peer outreach workers recruited 210 MSM in Chennai who completed an interviewer-administered psychosocial assessment battery and underwent HIV testing and counseling. More than one fifth (46/210) reported unprotected anal intercourse in the past 3 months, 8% tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 17 publications
4
88
1
Order By: Relevance
“…This discrepancy suggests that MSM with a lower literacy level in Chhattisgarh might be less aware of the available services and programs; it is also likely that their participation is more affected by stigma and discrimination. This study also revealed that illiterates subjects were likely to be at a higher risk of HIV, which is consistent with previous findings (14,(19)(20)(21). Therefore, these data suggest that the reach of intervention programs among MSM with a higher risk of HIV and lower or no education is probably less.…”
Section: Discussionsupporting
confidence: 92%
“…This discrepancy suggests that MSM with a lower literacy level in Chhattisgarh might be less aware of the available services and programs; it is also likely that their participation is more affected by stigma and discrimination. This study also revealed that illiterates subjects were likely to be at a higher risk of HIV, which is consistent with previous findings (14,(19)(20)(21). Therefore, these data suggest that the reach of intervention programs among MSM with a higher risk of HIV and lower or no education is probably less.…”
Section: Discussionsupporting
confidence: 92%
“…socially acceptable. Some heterosexual men do not consider maleto-male sex (including anal sex) as "sex" but rather "masti" or play, and may move fluidly between heterosexual and homosexual encounters (Khan, 2001;Patel, Mayer, & Makadon, 2012;Thomas et al, 2009). However, as in many low and middle-income countries, the health issues for MSM in India are under-studied and overlooked in part due to stigma and the criminalisation of homosexual intercourse (legislation enacted under British rule) up until 2009 (Baral, Sifakis, Cleghorn, & Beyrer, 2007;Chakrapani, Newman, Shunmugam, McLuckie, & Melwin, 2007;Setia et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Mumbai, 12 per cent of MSM seeking voluntary counselling and testing services were HIVinfected, and 18 per cent of the MSM screened in 10 clinics in Andhra Pradesh were found to be infected 16-18. It was found 8 per cent HIV prevalence in a sample of 210 MSM in Chennai recruited by peer outreach workers [3]. In the context of this disproportionally prominent level of HIV risk, it becomes extremely important to understand the socio-cultural factors that may exacerbate sexual risk among this group.…”
Section: Who Is Men Sex With Men (Msm)?mentioning
confidence: 99%